İLKOKUL 4. SINIF İNSAN HAKLARI, YURTTAŞLIK VE DEMOKRASİ DERSİ ÖĞRETİM PROGRAMININ ÖĞRETMEN GÖRÜŞLERİNE GÖRE DEĞERLENDİRİLMESİ (KASTAMONU ÖRNEĞİ) - Akdeniz, Betül (Sosyal Bilimler Enstitüsü, 2018)
ABSTRACT M.Sc. Thesis AN EVAULATION OF ELEMENTARY SCHOOL 4th GRADE ‘HUMAN RIGHTS, CITIZENSHIP AND DEMOCRACY’ COURSE’S CURRICULUM ACCORDING TO TEACHER OPINIONS (THE SAMPLE OF KASTAMONU) Betül AKDENİZ Kastamonu University Institute of Social Sciences Department of Turkish Language and Social Sciences Education Supervisor: Assoc. Prof. Dr. Selahattin KAYMAKCI Human Rights, Citizenship and Democracy in the Turkish Education System are taught to as two hours per week at the elementary schools 4th grade level. The aim of this research is to reveal the views of the primary school teachers on the application of the 4th grade Human Rights, Citizenship and Democracy curriculum. A mixed model was applicated in the research to reveal the current situation. The quantitative dimension of the research was realized with a total of 145 school teachers working in Kastamonu in 2015-2016 education term and the qualitative dimension was realized with 30 class teachers selected from the same sampling group. In the research "Human Rights, Citizenship and Democracy Course Curriculum Evaluation Scale" was used as the quantitative data collection tool and ‘Interview’ was used as the qualitative data collection tool. SPSS 22.0 program was used in the analysis of the quantitative data of the study, in this regard, not only descriptive statistics also parametric and non-parametric tests were utilized. Content analysis was used in the analysis of the qualitative data of the study. As a result of the research, it has been determined that the teachers have mostly positive opinions on the curriculum in the middle level. As a result, it has been analyzed that the teachers mostly have a favorable opinion on the middle level to the curriculum. While teacher views on the program showed a substantial difference in favor of women in terms of gender, there was no substantial difference according to factors such as graduation status, occupational experience, school settlement and school type. In addition, it has been stated that, as a result of the research, the teachers say that the course is very abstract, that it is over the student level, that it is not structured to be associated with everyday life and it is a structure that can be integrated into social studies. Moreover, it is determined that the course should be reduced to the student level and given to them at an early age, and the teachers regarded that the course as a necessary, owing to the educating of democratic citizens.
Keywords: Primary School, Human Rights, Citizenship and Democracy